2010
DOI: 10.1177/0093854810382751
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorder, Comorbidity, and Suicidal Behavior in Juvenile Justice Youth

Abstract: Results of collaborations with juvenile justice agencies nationwide were examined to provide generalizable estimates of psychiatric disorder and suicidality among justice system youth. Diagnostic assessments were aggregated from 57 sites (N = 9,819) from an automated computer-assisted self-interview (Voice Diagnostic Interview Schedule for Children). Disorder was predicted from setting type (system intake, detention, corrections), adjusting for demographic and offense characteristics, and for cross-site variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(216 citation statements)
references
References 41 publications
10
192
0
14
Order By: Relevance
“…Studies have shown that it is common to have 4 or more siblings in juvenile offenders, especially in those with psychiatric disorders (30). Living in large families increases the risk of juvenile's push to crime (31,32). In multiple-children families, the time parents can spare for each child is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it is common to have 4 or more siblings in juvenile offenders, especially in those with psychiatric disorders (30). Living in large families increases the risk of juvenile's push to crime (31,32). In multiple-children families, the time parents can spare for each child is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps because there is a high incidence of mental health disorders among children/youth involved in the juvenile justice system, it should be no surprise that suicidal ideation and suicidal behavior is higher among incarcerated juveniles than in the general population. It has been found that arrest for violence (Wasserman & McReynolds, 2006), repeat offending, juvenile justice involvement, and incarceration (Wasserman, McReynolds, Schwalbe, Keating, & Jones, 2010) are associated with suicidal ideation and behavior. Having a mental health issue with or without co-occuring substance use is likely a contributing factor to high suicidal ideation and suicide rates found in the detained juvenile population.…”
Section: Prevalence Rates Of Mental Health Issues In the Juvenile Jusmentioning
confidence: 99%
“…In regard to prevalence rates of suicide attempts, gender differences have been evidenced with higher rates in females (Bhatta et al, 2014;Wasserman & McReynolds, 2006;Wasserman, et al, 2010). In their review, Stokes et al (2015) found depression to be a predictor of suicidal ideation and suicidal behavior and in their meta-analysis of the MAYSI-2, Vincent et al (2008) found females significantly more likely than males to score above the caution cutoff on the Depression-Anxious and Suicide Ideation Scales.…”
Section: Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Burell & Moeser, 2014, p. 652) Trauma-informed care. Recognizing the psychological damage youth experience within the juvenile justice system, as well as the compounding nature of trauma the same youth experienced prior to entering the system, a focus on rehabilitation necessitates a consideration of significant mental health concerns (Wasserman, McReynolds, Schwalbe, Keating, & Jones, 2010). "It is clear that trauma is a core issue for many youth entering residential treatment, and is likely a major contributor to their emotional disturbance including trauma-related mental health problems" (Hodgdon, Kinniburgh, Gabowitz, Blaustein, & Spinazzola, 2013, p. 680).…”
Section: Psychological Damagementioning
confidence: 99%